Efficiency of food production under old and new technology: the case of farmers within and outside the Extension Package Program in Ethiopia - Alene, A.; Hassan, R.M. (Project MUSE, 2008)
This paper measures the technical, allocative, and economic efficiencies of farmers within and outside the Extension Package Program (EPP) in high and low potential agro-ecological zones in eastern Ethiopia. Within-group farmer efficiencies are analyzed relative to respective technologies to examine performance variation under traditional and improved technology. The results showed considerable efficiency variation not only among farmers outside EPP who mainly used traditional technologies, but also among farmers within the EPP who used improved technological packages. The results further showed that, in the high potential zone, farmers within the EPP used a superior technology, whereas both groups in the low potential zone used a homogenous technology, confirming the lack of appropriate technologies for less-favored agricultural areas. Education, credit, and the share of the leading cropping system are significantly related to production efficiency. The results suggest that an integrated credit, extension, and input supply system with appropriate technologies would raise food production efficiency.